IL-10 revisited in systemic lupus erythematosus - Biswas, Swayanka; Bieber, Katja; Manz, Rudolf Armin (Frontiers in Immunology, 2022)
IL-10 is a cytokine with pleiotropic functions, particularly known for its suppressive effects on various immune cells. Consequently, it can limit the pathogenesis of inflammatory diseases, such as multiple sclerosis (MS), inflammatory bowel disease, Crohn’s disease, and Epidermolysis bullosa acquisita, among others. Recent evidence however indicates that it plays dual roles in Systemic lupus Erythematosus (SLE) where it may inhibit pro-inflammatory effector functions but seems to be also a main driver of the extrafollicular antibody response, outside of germinal centers (GC). In line, IL-10 promotes direct differentiation of activated B cells into plasma cells rather than stimulating a GC response. IL-10 is produced by B cells, myeloid cells, and certain T cell subsets, including extrafollicular T helper cells, which are phenotypically distinct from follicular helper T cells that are relevant for GC formation. In SLE patients and murine lupus models extrafollicular T helper cells have been reported to support ongoing extrafollicular formation of autoreactive plasma cells, despite the presence of GCs. Here, we discuss the role of IL-10 as driver of B cell responses, its impact on B cell proliferation, class switch, and plasma cells.